From Blue Crab to Sustainable Blue Economy: How the Social Innovation Spiral Fosters Coastal Community Enterprise Susta inability in Eastern Thailand - Phuangprayong, Kanokwara; Noonin, Sanit (Thammasat Review, 2026)
The Sustainable Blue Economy has emerged as a transformative paradigm emphasizing the responsible use of marine resources while maintaining ecological integrity. However, its role in fostering grassroots social innovation within coastal communities remains underexplored. This study examines how community-led social innovation emerges, evolves, and generates socioeconomic and environmental impacts through the Social Innovation Spiral, drawing on a case study of a community enterprise on Ko Si Chang in Eastern Thailand. A mixed-method approach was employed, combining in-depth interviews with 25 key informants and survey data from 100 tourist consumers. The findings reveal that the Social Innovation Spiral operates as a dynamic and iterative mechanism enabling continuous learning, adaptive experimentation, and participatory development. The blue crab ice cream initiative demonstrates how seasonal oversupply and lowvalue marine resources can be transformed into value-added products through local knowledge, fair-trade sourcing, and circular waste management. Results indicate improved livelihood stability, more equitable income distribution, reduced waste, and stronger engagement with communitybased tourism. Survey findings confirm high consumer satisfaction, particularly in product uniqueness, engagement, and perceived social impact. This study contributes the Social Innovation Spiral to micro-level coastal contexts and empirically by demonstrating how Sustainable Blue Economy principles can be operationalized through community enterprises. It offers actionable insights for developing scalable, resilient, community-driven innovation models.